Bacterial cellulose-based biomaterials: From fabrication to application. (15th February 2022) - Chen, Chuntao; Ding, Weixiao; Zhang, Heng; Zhang, Lei; Huang, Yang; Fan, Mengmeng; Yang, Jiazhi; Sun, Dongping
Abstract: Driven by its excellent physical and chemical properties, BC (bacterial cellulose) has achieved significant progress in the last decade, rendering with many novel applications. Due to its resemblance to the structure of extracellular matrix, BC-based biomaterials have been widely explored for biomedical applications such as tissue engineering and drug delivery. The recent advances in nanotechnology endow further modifications on BC and generate BC-based composites for different applications. This article presents a review on the research advancement on BC-based biomaterials from fabrication methods to biomedical applications, including wound dressing, artificial skin, vascular tissue engineering, bone tissue regeneration, drug delivery, and other applications. The preparation of these materials and their potential applications are reviewed and summarized. Important factors for the applications of BC in biomedical applications including degradation and pore structure characteristic are discussed in detail. Finally, the challenges in future development and potential advances of these materials are also discussed. Graphical abstract: Based on its unique structure and properties like high elastic modulus, high specific surface area, low density, non-abrasive nature, ease of surface functionalization, high purity and crystallinity, high degree of polymerization, excellent biocompatibility and biodegradability, bacterial cellulose-based functional materials show a wide applications in biomedical materials, including wound dressing materials, artificial skin, vascular tissue engineering, bone tissue regeneration, drug delivery, and other applications in tissue engineering, et al. Unlabelled Image Highlights: Advances in fabrication and application of bacterial cellulose-based biomaterials are described. Conclusion relating to the progress in interesting and important fields is given. Challenges for future development of these materials and potential future advances are discussed.